P46 Effect of the COVID-19 pandemic on hip fracture patients in a Teaching London Hospital. (8th April 2021) - Umarji, Shamim; Sturley, Rhonda; Tsinaslanidis, Prodromos; Hing, Caroline B
Abstract: Introduction: Hip fractures are the commonest serious injury in older people, the commonest reason for older people needing surgery and the commonest cause of death following an accident. The NHFD is a national database whereby markers of care are recorded prospectively for patients over 60 years sustaining a hip fracture and requiring inpatient care, with a Best Practice Tariff linked to key performance indicators. The aim of this study was to review how care varied for patients sustaining a hip fracture during the COVID-19 pandemic compared to the equivalent time last year. Methods: Using the NHFD we compared data from March – May 2019 to the same period in 2020 during the pandemic at St George's Hospital. The study provides a snapshot of care during the pandemic. Results: There were more admissions and more discharges during the pandemic. There was an increase in time to theatre and subsequent reduction in BPT. There was also an increase in non- operative treatment for these patients. 6 patients were confirmed COVID-19 positive, one of whom died. There was a reduction in time to ortho-geriatrician review and also a reduction in delirium review post-operatively. Length of stay was also reduced. Conclusion: The COVID-19 pandemic had an effect on care provided to hip fracture patients. There was an increase in time and a deterioration in orthogeriatric review within 72 hours. The length of stay however improved due to improved focus on pathways and discharge processes. There was also a lower threshold to offer non- operative care wherever possible.